Overview of Body Dissatisfaction in Late Adolescence Tiktok Users - Munaiyyiroh, Lailiyah; Puspitaningrum, Noer Suci Endah (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
This study aims to find out the picture of body dissatisfaction in late adolescent TikTok social media users. This research uses Qualitative research methods using Intrinsic Case Studies. Data collection techniques were carried out using interviews and obsevation. The subjects in this study were late adolescents totaling 5 people aged 18-21 years and having a TikTok account. Body dissatisfaction can be defined as a negative attitude towards physical appearance resulting from the difference between the perceived perception of the body and the ideal body. In this study focused on late adolescence (age 18-21 years), According to an excerpt from Kumparan.com, in 2015 Lenhart, Smith, Anderson, Duggan and Perrin were heavy social media users in the 17-21 age group, with 87% accessing computers and 58% using smartphones.